Pengaruh Profitabilitas, Struktur Aset, Ukuran Perusahaan, Risiko Bisnis, Pertumbuhan Penjualan, Pertumbuhan Perusahaan, Likuiditas Terhadap Struktur Modal Pada Perusahaan Sektor Jasa Periode 2016-2018 - Monica Setiawati; Elvira Veronica (Jurnal Akuntansi)
The purpose of this research is to analyze the influence of profitability, asset structure, company size, business risk, sales growth, company growth and liquidity of the capital structure. The method used in this study is purposive sampling. The number of samples studied in this study was as much as 210 samples. The collection of data used in this study of secondary data came from the 70 financial statements of the service sector company in the period 2016-2018. Analysis of data from this study uses multiple linear regression. Based on the results of the study concluded that the asset structure has a significant positive influence on the capital structure, company growth and liquidity significantly negative effect on the capital structure, while the profitability, company size, business risk and sales growth has no influence on the capital structure.